Toward feedback-controlled anesthesia: Voltammetric measurement of propofol (2,6-diisopropylphenol) in serum-like electrolyte solutions - Kivlehan, Francine (2012)
Propofol is a widely used, potent intravenous anesthetic for ambulatory anesthesia and long-term sedation. The target steady state concentration of propofol in blood is 0.25-10 μg/mL (1-60 μM). Although propofol can be oxidized electrochemically, monitoring its concentration in biological matrixes is very challenging due to (i) low therapeutic concentration, (ii) high concentrations of easily oxidizable interfering compounds in the sample, and (iii) fouling of the working electrode. In this work we report the performance characteristics of an organic film coated glassy carbon (GC) electrode for continuous monitoring of propofol. The organic film (a plasticized PVC membrane) improved the detection limit and the selectivity of the voltammetric sensor due to the large difference in hydrophobicity between the analyte (propofol) and interfering compounds of the sample, e.g., ascorbic acid (AA) or p-acetamidophenol (APAP). Furthermore, the membrane coating prevented electrode fouling and served as a protective barrier against electrode passivation by proteins. Studies revealed that sensitivity and selectivity of the voltammetric method is greatly influenced by the composition of the PVC membrane. The detection limit of the membrane-coated sensor for propofol in PBS is reported as 0.03 ± 0.01 μM. In serum-like electrolyte solutions containing physiologically relevant levels of albumin (5%) and 3 mM AA and 1 mM APAP as interfering agents, the detection limit was 0.5 ± 0.4 μM. Both values are below the target concentrations used clinically during anesthesia or sedation. © 2012 American Chemical Society.